The effectiveness of a training program based on psychological resilience in reducing learned helplessness among a sample of university youth in Idlib Governorate (The International Journal for Scientific Research, 2025)
The current study aims to reveal the effectiveness of a training program in developing psychological resilience and reducing a learned helplessness among a sample of university youth in Idlib Governorate. The final study sample was (52) male and female students from Idlib University; they were randomly assigned to two groups; one experimental and the other control, each group consisted of 26 individuals (6 males and 20 females). The study used the Conner and Davidson Psychological Resilience Scale (CD-RISC) and the Quinless and Nelson learned Helplessness Scale (LHS) in addition to using the training program based on psychological resilience. The results showed differences between the average scores of the experimental group members and the average scores of the control group members on the psychological resilience scale and the learned helplessness scale after applying the program in Favor of the experimental group members, and differences between the average scores of the experimental group members in the pre- and post-measurements on the psychological resilience scale and the learned helplessness scale in Favor of the post-measurement. The results showed a continuous effect of the training program in developing psychological resilience and reducing learned helplessness among the experimental group members after the follow-up period. These results indicate the effectiveness of the training program used in this study.
Keywords: Psychological Resilience; Learned Helplessness; University Youth